The San Diego City Schools : enterprise resource planning return on investment - Jeffery, Mark, 1965- (SAGE Business Cases., 2008)
As the deputy chief of business services, Jeff Wiemann was part of the team that would implement the San Diego City School District's new enterprise resource planning (ERP) system. The district had just issued a request for proposal for finance, human resources (HR), and student information system software and implementation, a giant step forward in its efforts to alleviate the district's "overburdened and inadequate information technology."1 The district intended to implement a full ERP system, but planned to start with an HR module to mitigate risk. The HR module would require the least modification of any module, and would give the district's information technology staff valuable experience in deploying a major new capability.